Pengaruh Terapi Merajut Terhadap Penurunan Kecemasan Pada Lansia Di Dusun Krajan Desa Karanggeger Kecamatan Pajarakan Kabupaten Probolinggo - Nisaul Karimah; Rizka Yunita; Nafolion Nur Rahmat (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Elderly (elderly) is someone who has entered the final stages of the phase of life. This cycle can be seen from the symptoms of physical, psychological, and psychosocial changes. These changes will result anxiety. Anxiety is a feeling of fear that is not clear or even has no known cause. Knitting therapy is one method of lowering anxiety. The goal of this study was to examine how knitting therapy affected older people's anxiety levels. This research method uses a Pre-Experimental approach with aone group pre-post test.The population is 33 respondents and uses a simple random sampling technique. The research sample is 30 respondents. The instrument used is an anxiety questionnaire sheet withHamilton Anxiety Rating Scale (HARS) Indonesian version, then the data is collected through a process Editing, Coding, Scoring,andTabulating. The data obtained were analyzed using the testpaired T-Test. The results showed the average value of anxiety before knitting therapy was 16.63 while after knitting therapy the average value of anxiety was 6.50. The results of the data analysis test showed that there was an effect of knitting therapy on reducing anxiety in the elderly with -valeu = 0.000 <α = 0.05. Knitting therapy can be used to improve focus, and develop patience. knitting activities can train the left and right brain when doing the same movement, besides sitting quietly and focusing on knitting can reduce heart rate and blood pressure, so we feel relaxed and calm, this situation acts as a pain reliever. This also makes the feeling happy so that it can provide positive energy in a person, this is what makes the mood happy so that feelings of anxiety decrease easily. It is hoped that knitting therapy can be applied to fill the spare time of the elderly and future researchers canmake modifications to the therapeutic media that will be used, one of which can be equipped with making video media.